Prevalence, Risk Factors and Treatment Modalities of Peptic Ulcer Among Basic Medical Undergraduate Students in Delta State University, Abraka, Nigeria - KE, Edje; EG, Moke; AT, Eduviere; EK, Umukoro; BO, Edje (International Journal of Human and Health Sciences (IJHHS), 2022)
Objective: Smoking, alcohol consumption, coffee intake, non-steroidal anti-inflammatory drugs (NSAIDs) use and stress, which are risk factors of peptic ulcer disease (PUD), are usually associated with university students and could influence the prevalence of PUD. Hence, the current study is to identify the prevalence, risk factors and treatment options of PUD among basic medical undergraduate students of Delta State University, Abraka, as it will provide valuable epidemiological information. Materials and Methods: A descriptive cross-sectional survey on the prevalence and treatment modalities of peptic ulcer was conducted among 150 basic medical undergraduate students in Delta State University, Abraka, with the use of well-structured questionnaires. Statistical Package for Social Sciences (SPSS) version 21.0 software was used for data entry and analysis. Results and Discussion: Majority of the respondents were between the ages of 20-24 years, with a mean age of 22.3±3.17 years. Fifty-one of the 150 respondents reported to have ulcer (34%), mainly duodenal ulcer (62.7%). Majority of respondents reported the use of antacids (98%), proton pump inhibitors (PPI) (74.5%), and antibiotics (60.8%) in the management of peptic ulcer, however, combination drug therapy comprising antacids, PPI, and antibiotics was the mostly used (32; 62.7%). Conclusion: This study showed that the prevalence of peptic ulcer was 34%, with a gastric to duodenal ulcer ratio of 1:1.68, with intake of NSAIDs and alcohol consumption identified as the most associated risk factors amongst this students’ population. Effective treatment was achieved with appropriate combination therapies and patient compliance. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 61-66